Space Research Ethics - Sivula Oskari; Puumala Mikko; Palmroth Minna (Springer Science and Business Media LLC, 2026)
In this paper, we characterise the field of space research ethics and the moral and political landscape it operates on. To lay the groundwork for our ethical analysis, we begin by introducing the diverse ways space research is conducted in practice and by discussing ongoing changes in its operational environment. We note that space research is necessary to facilitate our modern way of life and is integral to green and digital transformation. Following that, we identify key space research ethical issues in different domains and suggest tentative elements that trigger the need for research to undergo ethical review, to forward discussion and debate. The difficulty is to find suitable guidelines that are defined clearly enough to be action-guiding but simultaneously broad enough to address the complexity and global nature of space research. In the long term, the most feasible approach may be to define a tailored set of research ethical guidelines for particular fields, particular space environments, and particular research goals. We further address how the collective and global nature of space activities adds additional layers of challenges regarding the research ethical responsibility of the scientific community. In this context, we suggest that research ethics is not only a set of specific moral codes developed as a professional ethic for researchers, but also an institutionalised way to guide and support research activities and the integrity of researchers to maintain trust within the research community and the society at large.